Radiofrequency ablation: A modern solution for thyroid nodule in Bangladesh (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Thyroid nodules are common and often require intervention when symptomatic, cosmetically concerning, or hormonally active. Surgery remains the standard treatment but carries risks of hypothyroidism, nerve injury, scarring, and prolonged recovery. Radiofrequency ablation (RFA) has emerged as a minimally invasive alternative with demonstrated safety and efficacy. RFA achieves substantial nodule volume reduction (50–80% within 6 months; sustained in >85% after 3 years) and provides symptom relief in over 80% of patients, with high cosmetic satisfaction. Thyroid function is largely preserved, minimizing the need for lifelong hormone therapy. Complications are uncommon (